Implementasi Blended Learning di Madrasah Aliyah Berbasis Pesantren - Sari, Pusvyta; Murod, Ahmad (Journal of Islamic Education, 2024)
This research aims to discribe the implementation of the blended learning method and the obstacles faced in Islamic boarding school-based MA Unggulan Al Imdad. This research is a qualitative research. The data collected by observation, interviews and documentation. The data obtained is sorted, annalised  and concluded to obtain a complete understanding. The research results show that blended learning at Islamic boarding school-based Madrasah Aliyah, MA Unggulan Al Imdad used the Flipped Classroom model during the COVID-19 pandemic and continued with the Lab-Rotation Model when it entered the new normal period. Facilities that frequently used are: computer laboratories connected to the internet network. The obstacles faced are the limited skills of teachers and students in blended learning using information and communication technology, lack of awareness and independence to focus on the subjects being taught, as well as limited computer laboratory facilities and infrastructure which must be used interchangeably